GLOBALISATION AND INNOVATIONS IN EDUCATION: PROS AND CONS - Lyudmyla Hnapovska; Valentyna Karpova (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article explores globalized educational landscape, considers trends and dwells on perspectives inherent to modern educational paradigm. Parallels between classical and innovative formats of education are drawn with special emphasis placed on the idea that proliferation of digital technologies and cultures is having a profound impact on attitudes and beliefs within teaching community, which prompts questions that need urgent answers. The paper analyses challenges set forward by computerization processes and highlights problems related to extensive use of digital technologies in teaching practices. Grounded in analytical overview of recent research papers related to the issues in question, the article suggests ways in which 'networked age' and ' global education' can get good in a classroom diversifying and altering the entrenched attitudes to teaching and learning foreign languages, and thus enabling teachers to appropriate their strategies and tactical steps to the need of educating and developing a moral, imaginative, creative and initiative individual with powerful cognitive potential. The paper claims that within the framework of the 21st century teacher-free digital pedagogics ensuring better educational quality can be received via thoroughly-measured balance between exploiting advantages of traditional teaching methodologies and applying info-communication techniques, creating global market for digitalized educational services, enhancing spread of global universities.